From Specific to General in Electoral Cycle Models - Caleiro, António Bento (2018)
The article considers a way of generalizing the, so-called, stylized, which is also a specific model of electoral cycles. This generalization consists on assuming that the output level does indeed exhibit persistence, i.e. its current value (may be) being a function (also) of its past value. In an integrated way, the consequences of this generalization are analyzed. Resumo Neste trabalho considera-se uma forma de generalizar o modelo, dito estilizado, o qual é também específico, de ciclos eleitorais. Esta generalização consiste em admitir que o produto, de facto, exibe persistência, i.e. o valor corrente (poder) ser função (também) do seu valor passado. De uma forma integrada, analisam-se as consequências daquela generalização.